Immediate Intravesical Instillation of Mitomycin C after Transurethral Resection of Bladder Tumor in Patients with Low-Risk Superficial Transitional Cell Carcinoma of Bladder - Barghi, Mohammad Reza; Rahmani, Mohammad Reza; Hosseini Moghaddam, Seyed Mohammad Mehdi; Jahanbin, Mehrnoosh (Urology Journal, 2009)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–> <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0cm; margin-bottom:.0001pt; text-align:right; mso-pagination:widow-orphan; direction:rtl; unicode-bidi:embed; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman"; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt; @page Section1 size:612.0pt 792.0pt; margin:72.0pt 72.0pt 72.0pt 72.0pt; mso-header-margin:36.0pt; mso-footer-margin:36.0pt; mso-paper-source:0; div.Section1 page:Section1; –> <!–[if gte mso 10]> <![endif]–> Introduction: The aim of this study was to evaluate the effect of immediate intravesical instillation of mitomycin C after transurethral resection of bladder tumor (TURBT) in patients with low-risk superficial transitional cell carcinoma (TCC). Materials and Methods: A total of 43 patients with low-risk superficial bladder cancer were randomly assigned into two groups after the surgery; 22 patients in group 1 were treated by immediate instillation of mitomycin C after TURBT, and 21 patients in group 2 received placebo. The two groups were compared using urine cytology and cystoscopy during the 24 postoperative months. Â Results: Recurrence within the first 3 months was reported in none of the patients in group 1 and 5 in group 2 (P = .02). Of these, 4 had recurrence of tumor in the primary site. At 12 and 24 months, there were 1 patient (4.5%) in group 1 and 8 (38.1%) in group 2 with recurrence (P = .007). We had no patients with multifocal recurrence in group 1, but 3 (14.2%) in group 2. Nine-month tumor-free survival rate was 95% in group 1. Three-, 6-, 9-, and 12-month tumor-free survival rates in group 2 were 76%, 71%, 66%, and 62%, respectively (P = .007). None of the patients in group 1 and 3 in group 2 (14.3%) experienced some degrees of tumor progression (P = .06). Conclusion: Immediate instillation of mitomycin C after TURBT seems to be effective in the recurrence reduction and increase of recurrence-free interval at least in short term.